Going Beyond Heroic Leaders in Development. (2nd June 2016) - Andrews, Matt
Summary: Leadership is an under‐studied topic in international development. When the topic is broached it is usually to support what might be called a "hero dependency": One or other individual is identified as the hero of a past event (or the hero‐to‐be of a future event). This article argues that this dependency is problematic, however, because (i) heroes have not emerged in many contexts for long periods and individuals who may have been considered heroes in the past often turned out less than heroic, (ii) heroes are at least as much the product of their contexts as they turned out to be the shapers of such, and (iii) stories about hero‐leaders doing special things mask the way such special things emerge from the complex interactions of many actors—some important and some mundane. Notions of hero‐leadership in development are less convincing when one appreciates these arguments. Referencing broader work on leadership (and some in the development space itself) the article calls development theorists and practitioners to go beyond the heroic leader perspective in thinking about who leads development. Copyright © 2016 John Wiley & Sons, Ltd.